Measuring organizational commitment and distributed leadership: a study in Malaysian secondary schools - Zulkefli, Siti Aminah; Mustakim, Siti Salina; Hassan, Aminuddin; Abdullah, Arnida; Basri, Ramli (Human Resource Management Academic Research Society, 2021)
The primary aim of this study is to determine the significant correlation between organizational commitment and distributed leadership among secondary school teachers in Malaysia. Using the instrument of Three-Dimensional Model (TCM) to measure the level of organizational commitment and Distributed Leadership Readiness Scale (DLRS) to measure the level of distributed leadership, the study specifically seeks to determine (1) the level of organizational commitment among secondary school’s teachers in Malaysia, (2) the level of distributed leadership among schools’ teachers in Malaysia, and (3) the relationship between distributed leadership and organizational commitment among secondary schools’ teachers in Malaysia from 350 respondents selected using a simple random stratified sampling technique. Data presented in this study were analyzed using a descriptive statistic to explain the level of variables and inferential statistics to find a correlation between these variables. Findings indicated that there is a significant correlation between organizational commitment and distributed leadership with r=.556, p=.000) at the strong level.